Uniting the Kingdom? : the making of British history - Grant, Alexander; Stringer, K. J. (Keith John) (Routledge, 1995)
A group of Britain's most prestigious historians assemble to explore the formation of the UK, its history and its identity. Traditional regional and chronological frontiers are broken down as mediev- alists, modernists and early modernists debate.